Acidosis orchestrates adaptations of energy metabolism in tumors - Größl, Sven; Kalis, Robert; Snæbjörnsson, Marteinn; Wambach, Leon; Haider, Jakob; Andersch, Florian; Schulze, Almut; Palm, Wilhelm; Zuber, Johannes (Science, 2025)
Malignant tumors are characterized by diverse metabolic stresses, including nutrient shortages, hypoxia, and buildup of metabolic by-products. To understand how cancer cells adapt to such challenges, we conducted sequential CRISPR screens to identify genes that affect cellular fitness under specific metabolic stress conditions in cell culture and to then probe their relevance in pancreatic tumors. Comparative analyses of hundreds of fitness genes revealed that cancer metabolism in vivo was shaped by bioenergetic adaptations to tumor acidosis. Mechanistically, acidosis suppressed cytoplasmic activity of extracellular signal-regulated kinase (ERK), thereby preventing oncogene-induced mitochondrial fragmentation and promoting fused mitochondria. The resulting boost in mitochondrial respiration supported cancer cell adaptations to various metabolic stresses. Thus, acidosis is an environmental factor that alters energy metabolism to promote stress resilience in cancer.